Improving procedural success rate of retrograde ethanol infusion in the vein of Marshall. (19th May 2022) - Poley, P; Krahnefeld, O; Agdirlioglu, T; Weil, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Retrograde ethanol infusion in the vein of Marshall (VOM) is a relatively new adjunctive therapy of atrial arrhythmias. The VOM is an epicardial left atrial vein. Its surrounding autonomic ganglia and proarrhythmogenic muscle fibers are accepted extrapulmonary triggers of AF and can be ablated by retrograde ethanol infusion. This facilitates the achievement of bidirectional mitral isthmus block. Moreover, it seems to improve outcomes in terms of rhythm stability if performed in addition to RF ablation in persistent atrial fibrillation. However, retrograde ethanol infusion in the vein of Marshall (VOM) can be technically challenging. Technical improvement of the procedure has the potential of higher primary success rate and therefore may secondary lead to better outcome of interventional therapy of persistent AF. Purpose: International experienced centers achieve an acute procedural success rate around 85%. The purpose of our investigation was to study the impact of adding procedural techniques to the standard procedure as described before on the acute procedural success. Methods: We analyzed all ethanol infusions in the VOM performed in our department between Nov 2019 and Nov 2021. Our standard approach resembles the technique published before primarily performed via a transfemoral access. If a VOM is angiographically not visible using the standard approach, we perform a rotational angiography. In case of negative angiography of the VOM, we try the atraumatic wiring assuming a typical anatomical location of the vein draining just proximal of the valve of Vieussens into the CS. If very proximal location of the VOM in the CS led to an instable catheter via transfemoral access we used transjugular access and a CRT-sheath. We collected data on additionally used techniques and their value for acute procedural success. All data are given as mean ± SD or number/percentages. Results: Ethanol infusions were mostly performed as standalone procedures (136/147, 92, 5%) or in a minority of cases as adjunctive therapy during RF-ablation. The ethanol infusion was succesful in 143 of the 147 patients (97%). In 21 patients (14%) extention of the technique exceeding the standard approach led to a succesful procedure. A rotational angiography revealed a previously not visible VOM in 5 patients (3, 4%). Atraumatic wiring of the angiographic negative VOM in typical position was successful in 11 patients (7, 5%). 5 patients (3, 4%) benefitted from a transjugular venous access. Periprocedural complications were rare. We observed no vascular access site complications or pericardial effusion/tamponade. One patient suffered from a transient ischemic attack one week after the procedure. Conclusions: Acute procedural success of ethanol infusion in the VOM amounted to 83% using the standard approach. We were able to improve the success rate to 97% by adding further imaging and modifying the technical approach while the positive safety profile remained.